Comparative pharmacokinetics study of orientin in rat plasma by UHPLC‐MS/MS after intravenous administration of single orientin and Trollius chinensis Bunge extract. (26th December 2017) - Zhao, Nan; Sun, Qi; Song, Yang; Wang, Lin; Zhang, Tingjian; Meng, Fanhao
Abstract: Orientin showed a broad array of biological activities, and it is the major bioactive compound in the Trollius chinensis Bunge. The aim of this study was to investigate the comparative pharmacokinetics of orientin after intravenous administration of single orientin and T. chinensis Bunge extract. Sample preparation involved a simple one‐step deproteinization procedure with acetonitrile. Chromatographic separation was achieved on a Waters BEH C18 column with a mobile phase consisting of acetonitrile and water containing 0.1% formic acid in an isocratic elution way. The detection was accomplished in multiple reaction monitoring mode with positive electrospray ionization. The pharmacokinetic properties of orientin were compared after intravenous administrations of pure orientin and T. chinensis Bunge extract to rats with approximately the same dosage of 10 mg/kg. The results of the study indicate that the pharmacokinetics of orientin in rat plasma show significant differences between two groups. This is useful for the clinical uses of therapeutic dosing of orientin and T. chinensis Bunge.